Impact of same-day ART initiation on medical care and medication discontinuation among patients with incident HIV infection or AIDS in Taiwan: A population-based cohort study - Chen-Han Chueh; Hsiao-Jou Yu; Yu-Wen Wen; Ming-Neng Shiu; Yi-Ying Chen; Shao-Chin Chiang; Yi-Wen Tsai (Journal of Infection and Public Health)
Background: Care retention and medication adherence are crucial for individuals living with human immunodeficiency virus (HIV). Discrepancies exist between real-world evidence and randomized trials regarding early antiretroviral therapy (ART) initiation and care retention. We investigated the effects of same-day ART initiation on care and medication discontinuation in new patients with acquired immunodeficiency syndrome (AIDS) and those newly infected with HIV. Methods: The two groups commenced ART from January 2017 to December 2021 in Taiwan. Data were collected from the National Health Insurance claims database. We defined care discontinuation as having no clinical visits for over 90 days since the last clinical visit and medication discontinuation as failing to pick up medication 30 days after the expected medication pick-up date. We used a doubly robust weighted Cox regression model to estimate the average hazard ratio for same-day ART initiation compared to rapid ART initiation within 7 days over a 12-month care- and medication-discontinuation risk horizon. Results: Among the 1528 HIV- and 5373 AIDS-group individuals, 1329 and 4494 initiated same-day ART, respectively. Same-day ART initiation did not impact care or medication discontinuation among HIV-infected patients. However, it was associated with a significantly lower hazard of care discontinuation (adjusted average hazard ratio [aAHR] = 0.86, 95 % CI: 0.74–0.99) and a higher, though not significant, hazard of medication discontinuation (aAHR = 1.14, 95 % CI: 0.86–1.52) among patients with AIDS. Conclusion: Same-day ART initiation demonstrates varying impacts on care and medication continuation. While it improves care retention, caution is advised regarding medication discontinuation among patients with AIDS.